Goffin cockatoos wait for qualitative and quantitative gains but prefer ‘better’ to ‘more’ - Auersperg, A. M. I. (The Royal Society, 2013)
Evidence for flexible impulse control over food consumption is rare in non-human animals. So far, only primates and corvids have been shown to be able to fully inhibit the consumption of a desirable food item in anticipation for a gain in quality or quantity longer than a minute. We tested Goffin cockatoos (Cacatua goffini) in an exchange task. Subjects were able to bridge delays of up to 80 s for a preferred food quality and up to 20 s for a higher quantity, providing the first evidence for temporal discounting in birds that do not cache food.